Financial forecasting using machine learning - Chang, Hin Keat (Nanyang Technological University, 2022)
Singapore’s economy is made up of 99% SME’s. They contribute to 70% of Singapore’s employment and 43% of the country’s Nominal Value. SME’s relatively simple structure allows them to respond quickly to the market as compared to larger corporations. On the flip side, their smaller size makes it difficult for SMEs to raise funds. Every business needs adequate capital for it to function. Financial forecasting can help calculate the financial needs of a business. Be it fixed capital or working capital, financial forecasting can make predictions on what a business needs to be successful. However, there are not any automated forecasting software in the market today.